Lymphedema in three previously Wuchereria bancrofti-endemic health districts in Mali after cessation of mass drug administration - Dolo, Housseini (BMC Infect Dis, 2020)
BACKGROUND: Lymphedema is a public health problem in countries with lymphatic filariasis (LF) including Mali. We studied the epidemiology and clinical presentation of lymphedema in three previously LF-endemic health districts of Mali after at least five consecutive rounds of mass drug administration (MDA) with albendazole and ivermectin. METHODS: From 2016 to 2018, we used passive and active case finding methods to identify lymphedema cases in three health districts with high pre-MDA LF prevalence: Kolondieba (66%), Bougouni (44%) and Kolokani (34%). RESULTS: Three hundred and thirty nine cases of lymphedema were identified, 235 (69.32%) through active case finding. Their median age was 56 years (range 2–90) and 286 (84.36%) were women. Lymphedema was reported in 226 (78.5%) people aged 41 years and older compared to 73 (21.5%) people below the age of 41 years (Chi(2) = 17.28, df = 5, p = 0.004). One hundred and seventy five cases of lymphedema were found in Kolondieba (66 per 100,000 people), 116 in Bougouni (19 per 100,000) and 48 in Kolokani (16 per 100,000). Stage III lymphedema was observed in 131 (38.64%), stage II in 108 (31.86%), stage IV in 46 (13.57%), stage I in 23 (6.78%), stage V in 21 (6.19%) and stage VI in ten (2.95%). In the three study districts, lymphedema affected the legs in 281 (82.89%), the arms in 42 (12.39%) and both in 16 (4.72%) (Chi2 = 13.63, p = 0.008). CONCLUSION: Health districts in Mali with the highest pre-MDA LF prevalences had the highest prevalence of lymphedema. Efforts to actively identify lymphedema cases should be scaled up in previous LF-endemic areas, and should be supplemented by a morbidity management and disability prevention plan at the peripheral health system level.